Benzoylation of polyphenylene oxide: characterization and gas permeability investigations - Bhole, Yogesh S.; Kharul, Ulhas K.; Somani, S. P.; Kumbharkar, S. C. (European Polymer Journal, 2005)
Benzoylation of polyphenylene oxide (PPO) was carried out with aromatic acid chlorides bearing specific groups at para-position (H methyl, Br, Cl and nitro), which differ in their polarity and bulk. The reaction conditions were optimized individually to get the high degree of substitution. These materials were characterized for thermal as well as other physical properties that are known to affect the gas permeation. In a series investigated, the nitrobenzoyl substitution on PPO resulted in the highest increase in glass transition temperature and the lowest thermal stability. An estimation of the packing density parameters-fractional free volume by density measurement and the d-spacing by X-ray diffraction analysis showed an increase in the packing density. The gas permeability was found to decrease in all the cases of benzoylation. The helium and oxygen based selectivities were increased, while CO2 based selectivities were decreased. The unusual trend observed in the gas permeation properties is explained on the basis of nature of substituent and the degree of substitution. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: benzoylation; Gas permeability; polyphenylene oxide; selectivity